Literary Migrations : Traditional Chinese Fiction in Asia (17th-20th Centuries) - Salmon, Claudine (Book collections on Project MUSE., 2015)
This book was written between 1981 and 1986, was first published in 1987, and has been out of print since. The Chinese version of it by Yan Bao et al., Zhongguo chuantong xiaoshuo zai yazhou, which also published in 1989, is also out of print. Since then more works especially in Chinese, Japanese, Korean, and Western languages have appeared which are mainly concerned with cultural exchanges between China and the countries of East Asia. Moreover a new interest has arisen among scholars from various countries on what has been termed "Asian translation traditions" and conferences are regularly organized on this topic. Judging from this rising interest in translation history, this book on traditional Chinese fiction in Asia, which sets the question of Asian translations into a general framework, and so far has no equivalent, is still of service to researchers.